In Using Leaders as Insider Witnesses Without Prosecuting Them, the Special Court for Sierra Leone May Have Legitimised Impunity - Ishmail Pamsm-Conteh (European Scientific Journal, ESJ, 2017)
There is a determination on the part of the international community that perpetrators of crimes during conflicts should not escape punishment for the roles they play during crises by either committing these offences themselves or by authorising their commission for such actions. Since most crimes are not documented, which makes it hard to acquire the proof or evidence required for conviction, the courts or tribunals rely on the testimony of individuals who witnessed the crimes that have been committed. Such individuals are known as insider witnesses. In cooperating with the prosecution, if they themselves had been among the perpetrators or part of the accomplices, they are sometimes given, though not in all cases, a reduced sentence, as part of the plea bargain with the prosecution. However, agreeing to testify does not exempt one from punishment. This is because there is an underlying principle that individuals who commit such crimes must be held accountable; the same principle is aimed at ending impunity for crimes committed during conflicts such as these that offend international law. The Mandate of Special Court for Sierra Leone was to prosecute those individuals who bear the greatest responsibility…, including those leaders who, in committing such crimes, have threatened the establishment of and implementation of the peace process in Sierra Leone. 1 However, Prosecutors at various stages of the trials engaged some of these leaders as insider witnesses, without prosecuting them. Consequently, these leaders evaded punishment for their alleged crimes. In this process, the Special Court may have legitimised impunity.